Urgensi Organisasi Pemuda Muhammadiyah dalam Politik dan Hukum di Jakarta: The Urgency of the Muhammadiyah Youth Organization in Politics and Law in Jakarta - Abdur Rahim; Ma'mun Murod Al-Barbasy; Andy Hermansyah; Zainal Muksin (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2022)
Muhammadiyah gives freedom to every organization member to exercise their rights in political life following all of their statements. The right to vote must be accounted for as citizens who act rationally and decisively, in line with the mission and interests of Muhammadiyah, for the sake of the nation and the state. This research uses normative juridical research methods (normative research). The nature of this research is descriptive, which aims to provide an overview of social phenomena regarding the role of psychiatrists in proving psychological violence in domestic violence crimes. Research data sources are primary legal materials, secondary legal materials and tertiary legal materials. The data collection method was carried out using document study techniques, which were analyzed using qualitative analysis techniques. Based on the research results, Muhammadiyah Youth chooses to strive in the life of the nation and state through efforts to develop or empower the ummah to achieve a civil society that is as strong as Muhammadiyah’s goal of achieving a truly Islamic society. Meanwhile, matters related to state policy as a process and result of the government’s political function will be followed through an appropriate and prudent approach following the principle of effective interest group struggle in the life of a democratic country that truly prioritizes the interests of the people and upholds institutional values.